DISKRESI MAJELIS KEHORMATAN NOTARIS TERKAIT PERLINDUNGAN PROFESI NOTARIS DALAM PERSPEKTIF HUKUM ADMINISTRASI - HARIANTO, DANI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2024)
The Honorary Council of Notaries is a body that has the authority to develop Notaries and has the right to give approval or rejection in matters of investigation and judicial process, especially with regard to taking photocopies of Deed Minutes and summoning Notaries to be examined in all matters relating to Notarial Deeds or Protocols made by Notaries. In Constitutional Court Decision No. 49/PUU-X/2013, the phrase "with the approval of the Regional Supervisory Council" is revoked and decided to be cancelled. Akil Mochtar, Chairman of the Panel of Judges of the Constitutional Court at that time, stated that this phrase had no binding legal force and was contrary to the 1945 Constitution. The Constitutional Court stated that the attitudes, titles, words, behaviour and actions of Notaries in relation to morals - eiwit, were not a matter of — socially acceptable. After the Constitutional Court's decision that many Notaries were "bullied" and "worked" by clients who had to be assisted in authenticating deeds. Many clients "bully" notaries with the help of their lawyers, and form notaries as "an outlet for their own legal dissatisfaction." Maybe the Notary Honorary Council should map out any legal issues that might involve notaries so that the notary's voice can be heard. The exercise of discretion by the MKN in defending the Notary profession requires understanding the Religiosity of Science with a prophetic approach so that it can apply moral values ??to build a dignified Notary profession ABSTRAKMajelis Kehormatan Notaris adalah institusi yang berwenang untuk membina Notaris dan berhak memberikan (approval) persetujuan atau penolakan dalam hal penyidikan dan proses peradilan, terutama berkaitan dengan pengambilan fotokopi Minuta Akta dan pemanggilan Notaris untuk diperiksa dalam setiap hal yang berkaitan dengan Akta atau Protokol Notaris yang dibuat oleh Notaris. Dalam Putusan MK No. 49/PUU-X/2013, frasa "dengan persetujuan Majelis Pengawas Daerah" dicabut dan diputus batalkan. Akil Mochtar, Ketua Majelis Hakim Mahkamah Konstitusi yang menjabat pada saat itu, menyatakan bahwa frasa tersebut tidak binding atau memiliki kekuatan hukum yang mengikat dan berseberangan dengan UUD 1945. Mahkamah Konstitusi menyatakan bahwa sikap, sebutan, ucapan, perilaku, dan perbuatan Notaris dalam kaitannya dengan moral—eiwit, bukan urusan—dapat diterima masyarakat. Setelah putusan Mahkamah Konstitusi bahwa banyak Notaris”bully” dan “dikerjai” oleh client yang harus dibantu dalam akta autentik. Banyak client “bully” Notaris dengan dibantu oleh pengacara mereka, danformation Notaris sebagai “pelampiasan atas ketidakpuasan hukum yang mereka lakukan sendiri”. Mungkin Majelis Kehormatan Notaris harus mapping permasalahan hukum apa saja yang mungkin melibatkan Notaris supaya voice of notary bisa terdengar. Pelaksanaan diskresi oleh MKN dalam melakukan pembelaan terhadap profesi Notaris diperlukan memahami Religiusitas Sains dengan pendekatan profetik sehingga dapat menerapkan nilai-nilai moral untuk membangun profesi Notaris yang bermartabat